Obtención y caracterización de bebidas alcohólicas a partir de quinua (Chenopodium tunkahuan), ataco (Amaranthus hybridus) y amaranto (Amaranthus caudatus l.), utilizando dos agentes fermentadores levadura (saccharomyces cerevisiae), hongo kombucha (medusomyces gisevi), en los Laboratorios Académicos de la Carrera de Ingeniería Agroindustrial de la Universidad Técnica de Cotopaxi e.n el periodo 2014-2015 - Bonifa Molina, Nelly Paola (2016)
In the present researching was obtained alcoholically drinks available on request to quinoa (chenopodium tunkahuan), ataco (amaranthus hybridus) and amaranto (amaranthus caudatus L.), using two biological agents provided by yeast (Saccharomyces cerevisiae), kombucha mushroom (medusomyces gisevi). The researching has an objective to identify the three best treatments, for this reason was done an organoleptic analysis where was evaluated: color, flavor, smell, appearance, acceptability, applying a survey to 148 students in the Agro-industrial Engineering, at Cotopaxi Technical University....